2021
DOI: 10.3389/fpsyt.2021.639202
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Surrounding Music of Patients With Anorexia Nervosa: A Survey-Based Mixed-Methods Analysis

Abstract: Anorexia nervosa (AN) is one of the main eating disorders. It has the highest mortality of all psychiatric disorders, and the success rates of current therapies are not fully satisfactory. Thus, there is a need for novel interventions. We investigated the attitudes surrounding music of 41 patients with clinically-diagnosed AN as well as their thoughts on the potential therapeutic uses of music using a questionnaire of 50 questions. Free text responses were qualitatively analyzed for reoccurring themes with NVi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Music as a self-regulation tool. Finally, the data of three integrated survey studies (Applewhite et al, 2020;Czepczor-Bernat et al, 2021;Krishna Priya et al, 2021), in which no interventions were used, support the discussed results of this review. Music-based regulation strategies were found to reduce the likelihood of unhealthy eating behaviors, depression and anxiety (Czepczor-Bernat et al, 2021).…”
Section: Receptive Mtsupporting
confidence: 68%
See 3 more Smart Citations
“…Music as a self-regulation tool. Finally, the data of three integrated survey studies (Applewhite et al, 2020;Czepczor-Bernat et al, 2021;Krishna Priya et al, 2021), in which no interventions were used, support the discussed results of this review. Music-based regulation strategies were found to reduce the likelihood of unhealthy eating behaviors, depression and anxiety (Czepczor-Bernat et al, 2021).…”
Section: Receptive Mtsupporting
confidence: 68%
“…This revealed that nonclinical use of music appeared to elicit both positive and negative emotions and memories. It was also found that music is beneficial in terms of important aspects of AN (coping with emotions, distraction, recovery) and that music triggers mainly positive emotions/memories but also negative memories/feelings in people with AN (Krishna Priya et al, 2021). Music is an integral and important part of life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies on the therapeutic use of music in helping patients with OCD should take the peculiarities of how music is received by people with OCD into account. Our systematic review has not yielded studies on qualitative aspects of the patients' perspective of and attitudes towards music, similarly to how they have been performed in other areas such as eating disorders [65]. To obtain specific answers from future research, the population should be well defined in terms of age (children, adolescents, adults or elderly people), severity and symptomatology.…”
Section: Future Directionsmentioning
confidence: 99%